2000
DOI: 10.1093/ajcn/71.6.1589
|View full text |Cite
|
Sign up to set email alerts
|

Human milk oligosaccharides are resistant to enzymatic hydrolysis in the upper gastrointestinal tract

Abstract: Background: Human milk oligosaccharides (HMOs) show a complexity and variety not found in milk of any other species. Although progress has been made in the past 3 decades with regard to identification and structural characterization of HMOs, not much is known about the physiologic functions of HMOs. Objective: As a prerequisite for biological activity in infant metabolism, HMOs have to resist enzymatic hydrolysis in the gastrointestinal tract. To assess the extent to which selected HMOs are hydrolyzed, we carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
270
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(280 citation statements)
references
References 36 publications
6
270
0
4
Order By: Relevance
“…However, Brand-Miller et al (1998) demonstrated with breath hydrogen methodology that most HMOs resist digestion in the small intestine of breast-fed infants and undergo fermentation in the colon. Studies in vitro have also confirmed that sialic acid is not released from the incubation of HMOs with pancreatic and mucosal enzyme mixtures (Engfer et al, 2000). The quantities of oligosaccharides in the urine and feces of breast-fed infants are also much higher than those in formula-fed infants (about 9:1 in urine and 62:1 in feces) (Newburg, 2000).…”
Section: Digestion and Absorption Of Sialic Acidmentioning
confidence: 88%
“…However, Brand-Miller et al (1998) demonstrated with breath hydrogen methodology that most HMOs resist digestion in the small intestine of breast-fed infants and undergo fermentation in the colon. Studies in vitro have also confirmed that sialic acid is not released from the incubation of HMOs with pancreatic and mucosal enzyme mixtures (Engfer et al, 2000). The quantities of oligosaccharides in the urine and feces of breast-fed infants are also much higher than those in formula-fed infants (about 9:1 in urine and 62:1 in feces) (Newburg, 2000).…”
Section: Digestion and Absorption Of Sialic Acidmentioning
confidence: 88%
“…Much less is known about the exact fate of eutherian milk oligosaccharides. Human milk oligosaccharides (HMOs) are resistant to enzymatic hydrolysis by brush border intestinal lactase (Engfer et al, 2000) and the majority appears to survive passage through the small intestine and to enter the colon, where they are subjected to fermentation by colonic bacteria (Brand-Miller et al, 1998).…”
Section: Urashima Fukuda and Messer Core Units And Lewis X (Galmentioning
confidence: 99%
“…HMO is of no energetic value for the infant since it resists enzymatic hydrolysis by host enzymes (Engfer et al ., 2000). This seemingly wasteful biosynthesis represents a paradox.…”
Section: Biome Engineering: Modifying the Nutrient Inputmentioning
confidence: 99%